2018
DOI: 10.3389/fimmu.2018.01566
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis Infection Mitigates Collagen-Induced Arthritis via Programmed Death 1-Mediated Immunomodulation

Abstract: Helminth infection induces Th2-biased immune responses and inhibitory/regulatory pathways that minimize excessive inflammation to facilitate the chronic infection of helminth in the host and in the meantime, prevent host hypersensitivity from autoimmune or atopic diseases. However, the detailed molecular mechanisms behind modulation on inflammatory diseases are yet to be clarified. Programmed death 1 (PD-1) is one of the important inhibitory receptors involved in the balance of host immune responses during chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 67 publications
2
28
1
Order By: Relevance
“…Presumably due to the higher burden of muscle larvae, the mortality was higher (Figure B) and IgG reduction was more remarkable (Figure ) in STAT6KO mice than in WT mice. Cheng et al reported that Ts reduced whole IgG and IgG2a levels, but did not affect the IgG1 level . This is in contrast to our result that Ts reduced both IgG1 and IgG2a levels.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Presumably due to the higher burden of muscle larvae, the mortality was higher (Figure B) and IgG reduction was more remarkable (Figure ) in STAT6KO mice than in WT mice. Cheng et al reported that Ts reduced whole IgG and IgG2a levels, but did not affect the IgG1 level . This is in contrast to our result that Ts reduced both IgG1 and IgG2a levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding other helminths, Th2 signals were reported to be essential for the anti‐arthritic effects . Recently, Cheng et al reported that Ts infection prevented CIA. Then, here we examined Th2‐dependency of the anti‐arthritic effects of Ts and demonstrated that Ts suppressed CIA in the genetic absence of STAT6 (Figure A,B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenocytes from wild-type (WT) and GdX-KO mice were suspended in Roswell Park Memorial Institute 1640 medium containing 10% newborn calf serum, 100 units/ml penicillin, and 100 units/ml streptomycin at 5 3 10 6 cells/ml in the presence or absence of denatured chick CII (50 mg/ml) for 72 h (10,11,23). For intracellular cytokine staining, splenocytes were stimulated with a cell activation cocktail with Brefeldin A (BioLegend) for 6 h, then the cells were stained with specific fluorescence antibodies as described in the figure legends.…”
Section: Cii-specific T-cell Differentiation and Cytokine Secretion Imentioning
confidence: 99%
“…Previous studies showed that IL-17 plays an important role in the generation of inflammatory pain (8,9). Overexpression of IL-17 exacerbates arthritis (10), whereas neutralization of IL-17 with an antibody effectively ameliorates RA (11). Clinical trials indicated that antibodies against IL-17 reduced synovial inflammation and prevented joint destruction in arthritis (12,13).…”
mentioning
confidence: 99%